Core cellular and tissue‐specific mechanisms enable desiccation tolerance in Craterostigma. (11th March 2023) - VanBuren, Robert; Wai, Ching Man; Giarola, Valentino; Župunski, Milan; Pardo, Jeremy; Kalinowski, Michael; Grossmann, Guido; Bartels, Dorothea
SUMMARY: Resurrection plants can survive prolonged life without water (anhydrobiosis) in regions with seasonal drying. This desiccation tolerance requires the coordination of numerous cellular processes across space and time, and individual plant tissues face unique constraints related to their function. Here, we analyzed the complex, octoploid genome of the model resurrection plant Craterostigma ( C. plantagineum ), and surveyed spatial and temporal expression dynamics to identify genetic elements underlying desiccation tolerance. Homeologous genes within the Craterostigma genome have divergent expression profiles, suggesting the subgenomes contribute differently to desiccation tolerance traits. The Craterostigma genome contains almost 200 tandemly duplicated early light‐induced proteins, a hallmark trait of desiccation tolerance, with massive upregulation under water deficit. We identified a core network of desiccation‐responsive genes across all tissues, but observed almost entirely unique expression dynamics in each tissue during recovery. Roots and leaves have differential responses related to light and photoprotection, autophagy and nutrient transport, reflecting their divergent functions. Our findings highlight a universal set of likely ancestral desiccation tolerance mechanisms to protect cellular macromolecules under anhydrobiosis, with secondary adaptations related to tissue function. Significance Statement: Here, we sequenced the model resurrection plant Craterostigma and identified genomic features underlying desiccation tolerance. We observed that desiccation induces a core set of pathways to protect the cellular macromolecules, but individual tissues utilize unique mechanisms to survive life without water.